Empowerment among adult patients with type 2 diabetes: age differentials in relation to person-centred primary care, community resources, social support and other life-contextual circumstances - Nina Simonsen; Anne M. Koponen; Sakari Suominen (BMC, 2021)
Abstract Background Rising prevalence of type 2 diabetes (T2D), also among younger adults, constitutes a growing public health challenge. According to the person-centred Chronic Care Model, proactive care and self-management support in combination with community resources enhance quality of healthcare and health outcomes for patients with T2D. However, research is scarce concerning the importance of person-centred care and community resources for such outcomes as empowerment, and the relative impact of various patient support sources for empowerment is not known. Moreover, little is known about the association of age with these variables in this patient-group. This study, carried out among patients with T2D, examined in three age-groups (27-54, 55-64 and 65-75 years) whether person-centred care and diabetes-related social support, including community support and possibilities to influence community health issues, are associated with patient empowerment, when considering possible confounding factors, such as other quality of care indicators and psychosocial wellbeing. We also explored age differentials in empowerment and in the proposed correlates of empowerment. Method Individuals from a register-based sample with T2D participated in a cross-sectional survey (participation 56%, n = 2866). Data were analysed by descriptive statistics and multivariate logistic regression analyses. Results Respondents in the youngest age-group were more likely to have low empowerment scores, less continuity of care, and lower wellbeing than the other age-groups, and to perceive less social support, but a higher level of person-centred care than the oldest group. Community support, including possibilities to influence community health issues, was independently and consistently associated with high empowerment in all three age-groups, as was person-centred care in the two older age-groups. Community support was the social support variable with the strongest association with empowerment across age-groups. Moreover, vitality was positively and diabetes-related distress negatively associated with high empowerment in all age-groups, whereas continuity of care, i.e. having a family/regular nurse, was independently associated in the youngest age-group only. Conclusion Person-centred care and community support, including possibilities to influence community health issues, supports empowerment among adults with T2D. Findings suggest that age is related to most correlates of empowerment, and that younger adults with T2D have specific healthcare needs.